Effects of calcination temperatures on structural and optical properties of zinc oxide, silicon dioxide and willemite synthesized by simple thermal treatment - Mustapha, Alibe Ibrahim (2016)
Phosphor host materials are subjects of continuing study in materials sciences because their physical and chemical properties and wide range of applications. Several methods and techniques have been applied for the synthesis of phosphor host materials. Most of these techniques are difficult to employ in a larger scale production due to the complicated procedures, longer reaction period, high reaction temperatures involved, toxic reagents and by–products which are potentially harmful and unfriendly to the environment. In this study, the Zinc oxide (ZnO), Silicon dioxide (SiO2) and Willemite were successfully synthesized using simple thermal treatment method from an aqueous solution containing only zinc acetate and silicon tetraacetate, poly(vinyl pyrrolidone), and deionized water. The characterization studies of the nanoparticles formed were carried out by Thermogravimetry analysis (TGA), X–ray Diffraction spectroscopy (XRD), Electron Dispersive X–ray spectroscopy (EDX), Transmission Electron Microscopy (TEM), Fourier Transform Infrared Spectroscopy (FT–IR), UV–Vis Spectrometer and PL Spectroscopy. The corresponding peaks of Zn, Si and O were observed in the EDX analysis of the sample which reveals their presence in ZnSiO4, while in the preparation of SiO2 the only peak of Si and O were observed. The Zn and O peaks in the EDX spectra ZnO reveals their presence. The XRD patterns confirmed the formation of nanoparticles of ZnO and Zn2SiO4 NPs. the XRD confirms that the SiO2 formed were in the amorphous state as there was no peak exhibited. The results from the FESEM and TEM shows that the particle size increased with the calcination temperature increased from 23.8 to 37.7 nm between 500 –750 °C in the case of ZnO, and the willemite phase formed at 1000 °C had 43.7 nm crystal size. The SiO2 particles calcined at 500–750 °C were <10 nm from the TEM images. The FT–IR spectra show only the principle absorption bands of Si–O–Si and Zn–O located at wavenumber less 1000 cm−1 respectively confirms the formation of ZnO, SiO2 and Zn2SiO4 NPs. The ZnO band gap energy was determined from UV–vis reflectance spectra using the Kubelka–Munk function and the band gaps were found to decrease with increase in calcination temperature due to particle size increased from 3.325– 3.245 eV calcined from 500–750 °C. The absorbance spectra were used to determine the band gap energy of SiO2 and Zn2SiO4. The wide band gap of 3.123– 4.352 eV for SiO2 samples calcine between from 500–750 °C was recorded. Willemite phase formed at 800, 900 and 1000 °C possessed a wide band gap of 5.460, 5.527 and 5.527 eV respectively. The PL analysis of ZnO NPs when excited at 300 nm reveals the various deep level defect originated from zinc interstitial while the PL analysis of Zn2SiO4 NPs at higher calcination temperature reveals deep level defects in the blue region related to oxygen vacancies often referred to as blue emission. The blue band observed for all samples in the PL analysis of SiO2 NPs have been believed to have originated from electron hole recombination of self–trapped exciton.